2008
DOI: 10.1007/s11751-008-0031-2
|View full text |Cite
|
Sign up to set email alerts
|

External fixator-assisted acute shortening with internal fixation for leg length discrepancy after total hip replacement

Abstract: We report a case of a 51-year-old lady, who underwent a femoral shortening using a fixator assisted blade plate after total hip replacement. The patient had a total hip replacement on the other side with previous revisions, which resulted in a leg length discrepancy. We used the above technique to control the shortening and preserve the mechanical and anatomical axis of the femur.Keywords External fixator Á Femoral shortening Á Total hip replacement Case reportA 35-year-old lady with a history of neglected dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Shortening of the ipsilateral thigh has been reported. 28 To the current authors' knowledge, this is the first reported series of patients who underwent contralateral lengthening for the treatment of symptomatic leg-length discrepancy after THA.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Shortening of the ipsilateral thigh has been reported. 28 To the current authors' knowledge, this is the first reported series of patients who underwent contralateral lengthening for the treatment of symptomatic leg-length discrepancy after THA.…”
Section: Discussionmentioning
confidence: 90%
“…In these instances, patients have few options. Kasis et al 28 described a patient with a 5-cm limb-length discrepancy who underwent shortening of the ipsilateral femur. A contralateral limb-lengthening osteogenesis was not possible because the contralateral (short) limb had undergone a longstem revision THA and therefore could not be treated with intramedullary limb lengthening.…”
Section: Discussionmentioning
confidence: 99%
“…introduced a surgical technique for contralateral leg lengthening to correct LLD. If contralateral leg lengthening is contraindicated, shortening of the THA leg may be considered.…”
Section: Direct Anterior Approach Total Hip Arthroplastymentioning
confidence: 99%
“…These include revision HA, ipsilateral limb shortening or contralateral HA. 22,23 Each of these procedures has its drawbacks or limitations, e.g. using insole lift can correct only small inequality while using lift outside the shoes for larger inequality is unsightly and when the shoes are off the inequality returns.…”
mentioning
confidence: 99%